3(x-6)=-x+2(x-6)

Simple and best practice solution for 3(x-6)=-x+2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-6)=-x+2(x-6) equation:


Simplifying
3(x + -6) = -1x + 2(x + -6)

Reorder the terms:
3(-6 + x) = -1x + 2(x + -6)
(-6 * 3 + x * 3) = -1x + 2(x + -6)
(-18 + 3x) = -1x + 2(x + -6)

Reorder the terms:
-18 + 3x = -1x + 2(-6 + x)
-18 + 3x = -1x + (-6 * 2 + x * 2)
-18 + 3x = -1x + (-12 + 2x)

Reorder the terms:
-18 + 3x = -12 + -1x + 2x

Combine like terms: -1x + 2x = 1x
-18 + 3x = -12 + 1x

Solving
-18 + 3x = -12 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-18 + 3x + -1x = -12 + 1x + -1x

Combine like terms: 3x + -1x = 2x
-18 + 2x = -12 + 1x + -1x

Combine like terms: 1x + -1x = 0
-18 + 2x = -12 + 0
-18 + 2x = -12

Add '18' to each side of the equation.
-18 + 18 + 2x = -12 + 18

Combine like terms: -18 + 18 = 0
0 + 2x = -12 + 18
2x = -12 + 18

Combine like terms: -12 + 18 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| (x^2-1)(x^2+8x+12)=0 | | 49x4/7 | | (X-1)(x+14)=0 | | 5/2/7 | | p/3+5=7 | | 3x+(-7x-3)=-153 | | 8-2-Y=6-4 | | (X+14)(x-1)=0 | | 2B-1A=70 | | x-2/5=-7/4 | | 10x-3x-2x=3x-13+2x | | -5x-9=6x-42 | | 7m^2=2m | | 900+Y+2=992 | | 4(x-3)=14 | | (5+9x)2=0 | | 234=(w+5)(w) | | 8-Y=5-3 | | 1A+2B=70 | | 6+Y=16-Y | | 3x-2y=17fory | | 5x+5x+3x=4x+1 | | 2+Y+4=12-5 | | -5m+3=-4.5 | | 8+17+x=180 | | (7x+20)(2x-9)=0 | | (5/14)/(3/4) | | F(7x)=7F(x) | | 4x-3=15-5x | | 0.5+2.75=17.75 | | 3(2x+1)=10x-0,6 | | 3/4(6+2x)= |

Equations solver categories